2021
DOI: 10.1177/01945998211065410
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Disparities and Vaccine Hesitancy in Black Americans: What Ethical Lessons Can Be Learned?

Abstract: Objective This state of the art review focuses on bioethical questions and considerations from research findings and methodological issues, including design and recruitment of participants, in studies related to COVID-19 vaccine hesitation in Black individuals. Ethical concerns identified were applied to otolaryngology with recommendations for improving health inequities within subspecialties. Data Sources An internet search through PubMed, CINAHL, and socINDEX was conducted to identify articles on COVID-19 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 79 publications
(118 reference statements)
4
29
0
11
Order By: Relevance
“…However, prior literature suggested that such disparities result from factors both within and outside of health care, such as concerns on the safety and the effectiveness of COVID‐19 vaccines, lack of insurance, financial restrictions, and distrust of healthcare systems. 18 , 19 Finally, as the outcome of interest of this study is receipt of at least on dose of COVID‐19, the findings may not entirely reflect the full vaccination status.…”
Section: Discussionmentioning
confidence: 90%
“…However, prior literature suggested that such disparities result from factors both within and outside of health care, such as concerns on the safety and the effectiveness of COVID‐19 vaccines, lack of insurance, financial restrictions, and distrust of healthcare systems. 18 , 19 Finally, as the outcome of interest of this study is receipt of at least on dose of COVID‐19, the findings may not entirely reflect the full vaccination status.…”
Section: Discussionmentioning
confidence: 90%
“…93 A 2021 review showed that, even with their high rates of COVID-19 vaccine hesitancy, Black individuals were still underrepresented in 62% of studies evaluating such hesitancy. 32 The Food and Drug Administration has recommended measures to enhance the diversity of clinical trial populations, such as incorporating diversity-related consideration in eligibility criteria, enrollment practices, and designs for phase III trials. 94 Finally, employing equity guidelines when designing and evaluating health care interventions can improve the effectiveness of health care interventions across diverse populations.…”
Section: Implications For Health Disparities Research In Otolaryngologymentioning
confidence: 99%
“…93 A 2021 review showed that, even with their high rates of COVID-19 vaccine hesitancy, Black individuals were still underrepresented in 62% of studies evaluating such hesitancy. 32…”
Section: Implications For Health Disparities Research In Otolaryngologymentioning
confidence: 99%
See 2 more Smart Citations